Determinants of Work Motivation and Its Implications on The Performance of High School Teachers in Riau Province (International Journal of Business and Information Technology, 2023)
This research aims to prove and analyze the improvement of teacher performance through improving the leadership of principals mediated by work motivation. The population in this research were high school teachers in Riau Province. The research method used in this research was descriptive survey method and explanatory survey with a minimum sample size of 220 respondents, with the data analysis method used is Structural Equation Modeling (SEM). The findings of the research were the principal's leadership has a positive and significant effect on work motivation with a contribution (R2) of 56%, the principal's leadership and work motivation simultaneously or partially have a positive and significant effect on teacher performance with a contribution (R2) of 62%, leadership the principal directly or indirectly through work motivation has a positive and significant effect on teacher performance with a contribution (R2) of 49%. The findings of the research also show that partially dominant work motivation affects teacher performance and is a partial mediating variable on the influence of the principal's leadership on teacher performance.